Eleventh marcel grossmann meeting:proceedinghs of the MG 11 meeting on the general relativity - Eleventh marcel grossmann meeting; Kleinert Hagen , ed. (World Scientific, 2008)
This proceedings volume of the eleventh meeting in the series, held in Berlin in 2006, highlights and records the developments and applications of Einstein's theory in diverse areas ranging from fundamental field theories to particle physics, astrophysics and cosmology, made possible by unprecedented technological developments in experimental and observational techniques from space, ground and underground observatories. It provides a broad sampling of the current work in the field, especially relativistic astrophysics, including many reviews by leading figures in the research community.
Keywords: Astrophysics; Cosmology; General relativity -Physics; Gravitation; Quantum gravity